HIGHER INCLUSIVE EDUCATION FOR PERSONS WITHSPECIALEDUCATIONAL NEEDS AS A SOCIO-PEDAGOGICALPROBLEM - Safarova , Zarina (Zamonaviy filologiya muammolari, 2025)
Higher education is one of the most effective ways of organizinglife.It gives freedom of life choice, spiritual and material independence, formsaworldview and life goals, develops a person's ability to adapt to a changingsocialsituation, gives life resilience and harmonizes existence, which is especiallyimportant for young people with disabilities.